Are Management Practices Failing or Aiding the Private Sector in South America ? - Hyland, Marie; Francis, David C.; Rodriguez Meza, Jorge (World Bank, Washington, DC, 2019)
An expanding body of literature has shown that better management practices can offer significant boosts to firms' productivity; this research illustrates that firms in South America are no exception. Using recent Enterprise Survey data from seven countries in South America (Argentina, Bolivia, Colombia, Ecuador, Paraguay, Peru, and Uruguay), the paper explores the various dimensions and drivers of management practices and analyzes how they are related to productivity. This is an important topic to investigate, given the lagging levels of productivity growth in the region. If management practices can boost firms’ productivity, this may be a cost-effective way to accelerate economic growth. The results show that improved management practices are associated with higher levels of productivity in all countries, and it is the impact of improved management specifically in larger firms that is driving the overall results. Indeed, in some countries, specifically Argentina, Paraguay, and Peru, it is only among larger firms that there is a positive link between management practices and productivity.